Successful Treatment of Pure Aortic Insufficiency with Transapical Implantation of the JenaValve - Bleiziffer, Sabine; Mazzitelli, Domenico; Nöbauer, Christian; Ried, Thomas; Lange, Rüdiger (The Thoracic and Cardiovascular Surgeon, 2013)
Transcatheter aortic valve implantation was predominantly developed for patients with severe calcified aortic stenosis, as most devices are designed to anchor within the native valve calcium. We report on a patient with pure insufficiency of a non-calcified aortic valve, in whom an anatomically oriented catheter valve was implanted successfully. The design of the prosthesis with position feelers engaging the native aortic valve leaflets proved to be suitable for the treatment of pure aortic insufficiency.
Keywords: aortic valve; transcatheter aortic valve implantation; transapical